Extremes on the benign-malignant tumour spectrum: Distinct transcriptomic landscapes between two common canine perianal neoplasms based on the hallmarks of cancer - Alexander F. H. Haake; Alina K. Loriani Fard; Vladimir M. Jovanovic; Michael Hummel; Sandro Andreotti; Achim D. Gruber (PLoS ONE, 2026)
The hallmarks of cancer describe stepwise changes in cellular functions and molecular pathways of tumour cells that undergo malignant progression. Although 14 hallmarks have been proposed, their manifestation at the molecular level across different tumour types remains incompletely understood. Here, we hypothesised that hallmark-associated transcriptomic signatures reflect the contrasting biological behaviours of a pair of a benign and a malignant tumour. To this end, we compared the two most common canine perianal tumours, the highly malignant apocrine gland anal sac adenocarcinoma (AGASAC) and the benign hepatoid gland adenoma (HGA). Spontaneous primary tumours were analysed using RNA-Seq (AGASAC n = 11, HGA n = 10) and a direct mRNA hybridisation panel (AGASAC n = 28, HGA n = 12). Large transcriptomic differences were observed in both the number of differentially expressed genes and enriched pathways. Surprisingly, transcriptomic differences based on the hallmarks of cancer were less pronounced that anticipated, particularly for “activating invasion and metastasis” and “inducing or accessing vasculature”. Only the HGAs showed a significant enrichment for “deregulating cellular energetics”. However, our data point towards a contrasting immune landscape between the compared tumours and a subgrouping of AGASACs associated with the inflammatory landscape. Overall, the transcriptomes of these two benign-malignant tumour extremes on the tumour spectrum contrasted each other in select aspects of the hallmarks. Still, their malignant or benign behaviours could not generally be mirrored on the mRNA level.